Polisi Wanita (Polwan): Reformasi Kesetaraan Gender Dalam Tubuh Polri - Edi Saputra Hasibuan (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2022)
As a state institution that has the authority to enforce law, the National Police must of course have a very dynamic nature, the presence of a member of the Police must be able to have a great effect on the community. Of course this is viewed from various aspects, both the Police as protectors, protectors, and servants of the community. This paper highlights the presence of female police officers (Polwan) which in fact is an important part of the progress of this institution itself. The fact that the Polri profession is a profession that requires strong mentality, determination, and dedication is not only found in men, but women are also able to become important figures who have a major influence on the development of the Polri itself. On this occasion the author tries to explore a little about gender equality, especially the existence of policewomen in the police, that to become public servants not only men, but women also have their role and existence in society. The issue of gender equality itself has always been a hot topic that is interesting to talk about, this cannot be separated from the dichotomy between men and women.